Screening of Germplasm Accessions for their Resistance to Leaf Hopper, Whitefly and Thrips Infesting Castor, Ricinus communis L. - Chandaragi, M. K.; Parmar, L. D.; Gangwar, G. P.; Patel, J. R.; Duraimurugan, P.; Patel, A. M. (International Journal of Economic Plants, 2025)
A field experiment was undertaken during September, 2023 to March, 2024 at Centre for Oilseeds Research, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat, India to screen the castor germplasm accessions against leafhoppers (22 no.), thrips (17 no.) and whiteflies (15 no) with checks. Out of 22 entries screened against leaf hoppers, 4 entries exhibited hopper burn grade 1 on 0–4 scale and were found resistant to leafhoppers. Leafhopper population among these accessions ranged from 11.0 to 419.2 leafhoppers 3 leaves-1 plant-1, whereas the susceptible check, DPC-9 recorded 369.2 leaf hoppers 3 leaves-1 plant-1 with hopper burn grade of 4 on 0–4 scale. The highest leafhoppers were in RG-4097 (419.2 leaf hoppers 3 leaves-1 plant-1) with a hopper burn grade of 4 (76 to 100% hopper burn). Four entries recorded a medium leafhopper population (30.4 to 170.7 leaf hoppers 3 leaves-1 plant-1) with hopper burn grade II (upto 11–25% hopper burn). The moderate to high infestation of thrips on top tender leaves and spikes were noticed on test entries. Among the accessions BCS-2 (0.1 whitefly top-1 leaf plant-1), PLM-23-1 (0.4 whitefly top leaf-1 plant-1), DPC-9 (1.3 whiteflies top leaf-1 plant-1), DCH 177 (5.4 whiteflies top leaf-1 plant-1) and 48-1 (9.4 whiteflies top leaf-1 plant-1), recorded significantly low population of whiteflies (pupae and adults) with damage grade of 0 on 0–5 scale and they were found resistant to whiteflies. These germplasm accessions identified as resistant to leaf hoppers, thrips, and whiteflies can be employed in breeding programs to develop resistant castor cultivars.